2021
DOI: 10.1007/s12144-021-01860-y
|View full text |Cite
|
Sign up to set email alerts
|

When it really counts: Investigating the relation between trait mindfulness and actual prosocial behavior

Abstract: Meta-analytical findings suggested a positive link between trait mindfulness and prosociality. However, most correlational studies on mindfulness and prosociality have relied on self-report measures. The present work aimed to address this serious limitation by investigating actual prosocial behavior. We further focused on mindfulness as a multi-dimensional personality trait to disentangle effects of different mindfulness aspects. In addition, we tested whether the relation between trait mindfulness and prosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…Noticeably, the effects sizes distributed across a wide spectrum, ranging from less than zero to about d = 1.60, twice the size of a conventionally large effect [24]. When focusing on observer-reported (instead of self-reported) prosocial behaviors, the association was considerably weaker, d = 0.37, 95% CI [0.19, 0.79] (see also [25]).…”
Section: Correlational Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…Noticeably, the effects sizes distributed across a wide spectrum, ranging from less than zero to about d = 1.60, twice the size of a conventionally large effect [24]. When focusing on observer-reported (instead of self-reported) prosocial behaviors, the association was considerably weaker, d = 0.37, 95% CI [0.19, 0.79] (see also [25]).…”
Section: Correlational Evidencementioning
confidence: 98%
“…For this latter type of prosocial behavior, Berry et al [22**] found no reliable meta-analytic effect of mindfulness interventions. The question thus remains, whether increased mindfulness increases costly prosocial behavior (see [25]).…”
Section: Experimental Evidencementioning
confidence: 99%
“…Furthermore, other studies found evidence of a negative impact of mindfulness on prosociality (Chen and Jordan, 2020;Guo et al, 2021;Hafenbrack et al, 2021;Poulin et al, 2021). Crucially, the inconsistency of the meta-analytical evidence on MM and prosocial behavior might be due to methodological issues and biases (e.g., employment of selfreport instead of behavioral measures and use of correlational instead of longitudinal studies) (Schindler and Pfattheicher, 2021;Schindler and Friese, 2022).…”
Section: Moral Behavior −mentioning
confidence: 99%
“…In mindfulness research, prosocial behavior has often been operationalized as helping behavior (Leiberg et al, 2011;Condon et al, 2013;Lim et al, 2015), altruistic redistribution of funds (Weng et al, 2013(Weng et al, , 2015, financial allocation (Hafenbrack et al, 2020), reparative behavior (Hafenbrack et al, 2021), or monetary donation (Ashar et al, 2016;Chen and Jordan, 2020;Iwamoto et al, 2020;Schindler and Pfattheicher, 2021).…”
Section: Mindfulness and Socio-moral Behavior As Measured With Reward...mentioning
confidence: 99%
“…More importantly, because we aimed at assessing people's general way of acting during the COVID-19 pandemic in terms of social distancing, the scale concerning concrete social distancing was too specific and too context-dependent for measuring these traits; for instance, by presuming the weather to be good the next few days when the study was conducted over several weeks. Hence, the scale rather measured people's momentary behavior, or more specifically their momentary behavioral intentions, which however have been shown to vary widely and to not correspond to people's average behavior (Fleeson, 2004;Schindler & Pfattheicher, 2021). Retrospectively, it would have been a better choice to employ a different scale targeting people's typical behavior─not susceptible to situational factors─which is the reason why we relocated the according results to the Supplemental Material.…”
Section: Limitationsmentioning
confidence: 99%